2021
DOI: 10.1016/j.cub.2021.03.057
|View full text |Cite
|
Sign up to set email alerts
|

Population turnover facilitates cultural selection for efficiency in birds

Abstract: Highlights d We conducted a cultural evolution experiment using captive great tits d Gradual replacement of individuals promoted the spread of efficient cultural variants d Immigrants played a role as adopters rather than innovators of efficient variants d Turnover might be a general mechanism in the cultural evolution of efficiency

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
48
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(60 citation statements)
references
References 41 publications
3
48
0
Order By: Relevance
“…However, a number of suppliers, including Loligo Systems, Cogniot, Eccel and Sparkfun, produce RFID HATs for the Raspberry Pi that can read ISO 11784 certified PIT tags for animal identification (at both 125 kHz and 134.2 kHz), and are already available for less than €1/tag. This offers a wide range of possible experimental manipulations, where unique individuals are automatically detected and in turn these detections can be programmed to trigger specific actions, including playback of audio or visual stimuli, controlling servos and providing commands to external devices (see Bolaños et al., 2017; Chimento et al., 2021; Noorshams et al., 2017; Silasi et al., 2018; Youngblood, 2020).…”
Section: Guidelines Pointers and Considerations For Implementing The Raspberry Pimentioning
confidence: 99%
See 1 more Smart Citation
“…However, a number of suppliers, including Loligo Systems, Cogniot, Eccel and Sparkfun, produce RFID HATs for the Raspberry Pi that can read ISO 11784 certified PIT tags for animal identification (at both 125 kHz and 134.2 kHz), and are already available for less than €1/tag. This offers a wide range of possible experimental manipulations, where unique individuals are automatically detected and in turn these detections can be programmed to trigger specific actions, including playback of audio or visual stimuli, controlling servos and providing commands to external devices (see Bolaños et al., 2017; Chimento et al., 2021; Noorshams et al., 2017; Silasi et al., 2018; Youngblood, 2020).…”
Section: Guidelines Pointers and Considerations For Implementing The Raspberry Pimentioning
confidence: 99%
“…Lertvilai (2020) built an automated recording device specifically for autonomous zooplankton surveys in the wild. And Hermann et al (2020) developed F I G U R E 3 A diverse range of Raspberry Pi applications: (a) plant phenotyping(Tausen et al, 2020), (b) high-throughput animal recordings(Jolles et al, 2017), (c) a dedicated plant growth cabinet(Ghosh et al, 2018), (d) a 3D-printed microscope (FlyPi; MaiaChagas et al, 2017), (e) an RFID-equipped birdfeeder(Youngblood, 2020), f) long-term monitoring of fish behaviour(Martorell-Barceló et al, 2021), (g) automated bird puzzle boxes(Chimento et al, 2021), (h) an autonomous underwater camera system(Lertvilai, 2020), (i) automated quantification of fly climbing behaviour(Spierer et al, 2021), (j) a field audio recorder for bioacoustics(Bradfer-Lawrence et al, 2019;Whytock & Christie, 2017), (k) an operant conditioning device for wild mesocarnivores(Stanton et al, 2020), (l) autonomous ecosystem monitoring(Sethi et al, 2018), (m) closed-loop virtual reality(Tadres & Louis, 2020), (n) long-term recording of fish from birth (K. Laskowski & J. Jolles, pers. comm.…”
mentioning
confidence: 99%
“…This new tool-using technique apparently originated from widely present leaf-sponging behaviour [ 53 ], and further work showed that the new technique continued to spread through social learning, most likely because moss tools are faster to manufacture while offering increased absorption capacity [ 54 , 55 ]. Finally, a recent experimental study found a positive relationship between population turnover and the cultural evolution of efficiency in great tits [ 56 ]; knowledgeable residents more often innovated an efficient alternative foraging behaviour, which was then adopted by less experienced immigrants, so that population turnover greatly increased the probability that this efficient behaviour invaded populations. This result echoed an older study in blueheaded wrasse, in which naive individuals better re-sampled options for mating sites compared with experienced, resident fish [ 57 ].…”
Section: Evidence For Cultural Evolution In Animalsmentioning
confidence: 99%
“…[ 55 ] increasing reward (liquid absorption) organism great tit ( Parus major ) foraging puzzle latency to reward (food item) Chimento et al . [ 56 ] organism bighorn sheep ( Ovis canadensis ) moose ( Alces alces ) migration routes increasing reward (food availability via knowledge of phenology) Jesmer et al . [ 59 ] organism and behaviour chimpanzee ( Pan troglodytes ) extractive tool foraging increasing reward behavioural structure (bimanual coordination) Humle & Matsuzawa [ 68 ] organism and behaviour chimpanzee ( Pan troglodytes ) extractive tool foraging latency to reward behavioural structure (no.…”
Section: Defining and Quantifying Efficiencymentioning
confidence: 99%
See 1 more Smart Citation